Loess distribution and related Quaternary sediments in the Carpathian Basin - Lehmkuhl Frank; Bösken Janina; Hošek Jan; Sprafke Tobias; Marković Slobodan B.; Obreht Igor; Hambach Ulrich; Sümegi Pál; Thiemann Arne; Steffens Stefanie; Lindner Heiko; Veres Daniel; et al. (2018)
Supraregional (palaeo)geoecological studies require detailed knowledge of the distribution of aeolian sediments and their sources. Such spatial data can be visualised and shared in maps, but often these are constrained in their resolution or extent. This is the case for the Carpathian Basin, where cross-border maps are not detailed enough to answer many research questions. Problems occur especially along political borders due to different geological mapping standards and varying lithological definitions. Using a Geographic Information System (GIS), we compiled a map showing the distribution of loess and related Quaternary sediments in the Carpathian Basin, with unprecedented detail. We vectorised and analysed existing data (mainly from geological maps) and combined and transferred these into a common (loess) sediment classification system. This cross-border map shows the distribution of aeolian sediments in the Carpathian Basin at a scale of 1:1,500,000. For the northwestern and the southern Carpathian Basin, we added maps that clarify the extent of late Pleistocene and Holocene terrace and floodplain deposits, which were merged in the to highlight the predominant dust source areas for this region.